1911 оны Монголын үндэсний хувьсгалд нөлөөлсөн гадаад хүчин зүйлс - Төмөрхүлэг, Т. (Historia Mongolarum, 2006)
1911 оны Монголын үндэсний эрх чөлөөний хөдөлгөөнд Төвдийн хүчин зүйл дам нөлөөлж байсныг энэ өгүүлэлд гаргахыг хичээв External factors of the Mongolian National Revolution of 1911. It has been commonly viewed by the historians of the USSR and the People’s Republic of Mongolia that the national liberation movement of Mongolia in 1911 was influenced directly by the 1905 Revolution in Russia. However, the historians failed to provide convincing evidences supporting such argument. The argument, influenced by the political and ideological dogmatism of the given time was made in an attempt to pleas Lenin’s statement 1905 Revolution awakened all Asia... However, the disclosure archives, especially those in Russia, has enabled today's historians to research an suggest new conclusions on the subject. For instance, documents found in the Russia Empire’s foreign policy archives have brought the author to the conclusion that the 1905 Revolution in Russia had no impact at all on the Mongolian national liberation movement 1911. The realistic evidence lies in the fact that Mongolia had nor the intelligentsia with Further, the author bases himself on the new conclusion that the Mongolian national liberation movement was effected by the Tibetan factors. The cultural and religious bonds maintained for many hundred years between theses two nations (Mongolians and Tibetans) who were subjects of the Mandchuria Dynasty, became the foundation for establishing political relations at the beginning of XX Century. Based on authentic documents, the author has made attempts to prove Dalai Lama XIII were strengthened from 1904 and the parties came to agreement to cooperat in gaining independence from the imperialistic dynasty. Thus, this argument is raised for the first time in the modern history of Mongolia.